2020
DOI: 10.14202/vetworld.2020.2346-2352
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the benefits and production challenges of working donkeys in smallholder farming systems in Kenya

Abstract: Aim: The aim of the study was to determine the benefits of keeping donkeys and associated production challenges under a smallholder farming system in Kenya. Materials and Methods: A descriptive study was conducted with smallholder farmers keeping donkeys in 13 administrative locations in Kirinyaga County. Data were collected using a questionnaire guide in 13 focus group discussions (FGDs) using participatory epidemiological methods. The FGDs comprised 8-12 participants who were donkey owners. Data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…Majority of the villager who are used to the domestication of donkeys have stopped because of the increase in price, disease and thefts. This is line with the findings of Gichure, Onono, Wahome, and Gathura (2020) who found that some of the major factors that threaten the existence of donkeys in Africa are theft for slaughter, disease incidence, road accidents and malicious cutting. Similarly, Khaleel et al (2020a) also found that the population of donkeys were drastically decreasing due to the overexploitation for its hide and industrialisation in Northern Nigeria.…”
Section: The Importance Of Donkeys In the Areasupporting
confidence: 92%
“…Majority of the villager who are used to the domestication of donkeys have stopped because of the increase in price, disease and thefts. This is line with the findings of Gichure, Onono, Wahome, and Gathura (2020) who found that some of the major factors that threaten the existence of donkeys in Africa are theft for slaughter, disease incidence, road accidents and malicious cutting. Similarly, Khaleel et al (2020a) also found that the population of donkeys were drastically decreasing due to the overexploitation for its hide and industrialisation in Northern Nigeria.…”
Section: The Importance Of Donkeys In the Areasupporting
confidence: 92%
“…There is currently no research comparing the type of load carried and the weight of that load. However, working donkeys that transport different types of loads experience different impacts on their health and welfare (7,24,25,27,(34)(35)(36)(37). For example, donkeys used in brick transport are 2.5 times more likely to have moderate to deep skin lesions and 3.4…”
Section: Discussionmentioning
confidence: 99%
“…For crop cultivation, equid manure has long been valued as a fertiliser: it is richer in nitrogen than cow manure, and because of the large amount of organic matter is a good soil conditioner, and substrate for vermicosting and mulch. For example, in central Kenya, manure from donkeys was often used as fertilizer for farmed crops such as rice (Gichure et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%